Photonuclear production of Pm-149 - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L. (Вопросы атомной науки и техники, 2015)
¹⁵³Sm is successfully used for palliative treatment of patients with bone metastases and pain. ¹⁵³Sm is being produced in the reactors by means of irradiating of ¹⁵²Sm. In radio-labelled radiopharmaceuticals per each isotope of ¹⁵³Sm contained about 1000 atoms of the ¹⁵²Sm, which greatly influence the kinetics of its transport into the tumor. Production of ¹⁴⁹Pm isotopes that do not contain impurities of other isotopes, it was implemented using photonuclear reactions. The characteristics ¹⁴⁹Pm is practically coincides with the parameters of ¹⁵³Sm. The irradiation of neodymium of natural isotopic composition was carried out by means of bremsstrahlung with a maximum energy of 12.5 MeV. For production of ¹⁴⁹Рm the reaction ¹⁵⁰Nd(γ,n)¹⁴⁹Nd (T1/2=1.73 hours) → ¹⁴⁹Pm was used. Reaction ¹⁴⁸Nd(γ,n)¹⁴⁷Nd (T1/2=10.93 days) → ¹⁴⁷Pm (T1/2=2.62 years) will lead to low activity ¹⁴⁷Pm provided daily extraction ¹⁴⁹Pm. The rare earth elements of cerium group successfully are separated in a multistage extraction column using a normal tributyl ester of phosphoric acid.